Advancing blood-brain barrier-on-a-chip models through numerical simulations - Carvalho, Violeta Meneses (2024)
Researchers have placed engineered or natural tissues within microfuidic chips originating the so-called organ-on-a-chip (OoC) devices. With this technology, organ models can be subjected to phenomena that replicate the complex in vivo biological environment. Furthermore, the OoC devices constitute a more valuable, cost-efective and ethical option when compared to assays performed in animal models for disease research and drug discovery. However, there are still many challenges in replicating some organs/diseases in vitro such as the Blood–Brain Barrier (BBB), given its complexity and structure. Despite the difculties, many eforts have been made to develop improved in vitro BBB-on-a-chip models to investigate several neurological disorders. In the present review, a summary of the progress made in the development of BBB-on-a-chip is provided focusing on the importance of using numerical simulations for obtaining improved models and better planning the experimental assays. In addition, the future perspectives and current challenges are provided.